Implementasi Hukum Dalam Dampak Penanggulangan Lingkungan Akibat Perusahaan Batubara di kabupaten Batanghari provinsi Jambi - Ternando, Albi; Irawan, Agus (Universitas Batanghari Jambi, 2024)
Jambi Province is one of the provinces in Indonesia with natural mining wealth which has a lot of natural resources stored in it and has very good potential for energy sources that can be managed well, such as natural resources which contain coal, one of which is in the region. Kotoboyo village, Dalam sub-district XXIV, Batanghari Regency, Jambi Province, is one of the largest coal producing areas in Indonesia, this area has been very productive in recent years, several coal mining companies have been located in the area, this does not necessarily mean that the results are high. Coal reserves can have a positive impact on the people who live in the surrounding area. In fact, there tends to be no visible environmental impact on the community. The mining activity process around the mine still uses national public road access, causing traffic jams for kilometers and disrupting public road traffic. Local communities, the Central, Regional Government and the Ministry of Energy and Mineral Resources should work together firmly to face the polemics that occur in the community as quickly as possible to provide solutions so that special road access to reduce the massive mobility of coal mining movements is immediately realized for the prosperity of the community's economic movement.